2009
DOI: 10.3748/wjg.15.5455
|View full text |Cite
|
Sign up to set email alerts
|

Reasons of PEG failure to eliminate gastroesophageal refluxin mechanically ventilated patients

Abstract: AIM:To investigate factors predicting failure of percutaneous endoscopic gastrostomy (PEG) to eliminate gastroesophageal reflux (GER). METHODS:Twenty-nine consecutive mechanically ventilated patients were investigated. Patients were evaluated for GER by pH-metry pre-PEG and on the 7th post-PEG day. Endoscopic and histologic evidence of reflux esophagitis was also carried out. A beneficial response to PEG was considered when pH-metry on the 7th post-PEG day showed that GER was below 4%. RESULTS:Seventeen patien… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2013
2013
2021
2021

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 24 publications
0
3
0
Order By: Relevance
“…In return, gastroesophageal reflux can be exacerbated by supine positioning of the patient [ 13 ], as it will induce relaxation of the lower esophageal sphincter. Wang et al [ 14 ] demonstrated that 40% of patients with type II diabetes mellitus showed symptoms of reflux, as well.…”
Section: Discussionmentioning
confidence: 99%
“…In return, gastroesophageal reflux can be exacerbated by supine positioning of the patient [ 13 ], as it will induce relaxation of the lower esophageal sphincter. Wang et al [ 14 ] demonstrated that 40% of patients with type II diabetes mellitus showed symptoms of reflux, as well.…”
Section: Discussionmentioning
confidence: 99%
“…Percutaneous endoscopic gastrostomy is generally regarded as safer than the traditional surgical gastrostomy. However, several complications have been documented such as peristomal wound infection, pneumonia, gastroesophageal reflux disease (GERD), buried bumper syndrome, gastroparesis and bleeding [2–4].…”
Section: Introductionmentioning
confidence: 99%
“…Endoscopy has excellent specificity for diagnosing GERD, especially when patients have GERD with erosive esophagitis (EE) [5]. In previous studies, patients have not received the same pre‐ and post‐PEG endoscopic assessment for GERD [4,8]. In addition, most studies only evaluate the incidence of gastroesophageal reflux episodes after PEG [10–12].…”
Section: Introductionmentioning
confidence: 99%